Acceptability of Cabbage Chips Among HE Senior High School Students in Bestlink College of the Philipines S.Y 2021-2022: Vol.3, No.1D (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Cabbage is high in vitamin K, which can affect the ability of blood thinners like warfarin to prevent blood clots and vitamin A. It also provides fibre, folate, potassium, magnesium, and more doses. There are only 33 calories in a cup of cooked cabbage, which is low in fat, keeping you looking healthy, toned, blemish-free, and glowing. To make cabbage chips, tear leaves from the head of the cabbage into large pieces, toss with olive oil, season with salt, and arrange in a single layer on two wire racks set on rimmed baking sheets. Bake until leaves darken slightly and get crisp, removing them as they brown, 25 to 35 minutes. Purple cabbage, in particular, is a powerful brain food containing vitamin K and the antioxidant anthocyanin, which boosts mental function and concentration. Vitamin K, an often-forgotten vitamin, can also improve your defence against Alzheimer's and dementia. A study of food acceptability and the evaluation of its sensory measures is explained by the fact that foods are typically served in a situation, during a meal, and that the consumer typically brings to the dining situation a host of expectations based on previous experience, product and nutrition information, and packaging, all of which can influence food starting to love. Both male and female respondents have the same number, 25 or 25%, who came from the  students of Bestlink College of the Philippines. Keywords: cabbage chips, cabbage
Keywords: cabbage chips; cabbage